ANALYSIS OF THE EFFECT OF TOTAL QUALITY MANAGEMENT ON MANAGERIAL PERFORMANCE WITH PERFORMANCE MEASUREMENT SYSTEM AS AN INTERVENING VARIABLE ON PERUMDA AIR MINUM TIRTA MOEDAL SEMARANG - Apridita, Kausarina; Karyanti, Tutik Dwi; Ciptaningtias, Arum Febriyanti; Astungkara, Agni (Applied Accounting and Management Review (AAMAR), 2024)
This study aims to determine the effect of Total Quality Management, especially focus on customers, quality obsession, long-term commitment, and continuous improvement on managerial performance mediated by a performance measurement system at Perumda Air Minum Tirta Moedal Semarang. There are 38 respondents selected based on the purposive sampling technique. Methods of data collection by distributing questionnaires and interviews. This study used a data quality test which consisted of validity and reliability tests, then used the classical assumption test which consisted of a normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing is done by t-test, f-test, determinant coefficient test, and path analysis (Path Analysis). The results of this study state that the performance measurement system cannot mediate the relationship between customer focus and managerial performance. The performance measurement system cannot mediate the relationship between quality obsession with managerial performance. The performance measurement system cannot mediate the long-term commitment relationship to managerial performance, the performance measurement system cannot mediate the continuous improvement relationship to managerial performance.